APPLICATION PROTOTYPE SEARCHING AND BOOKING BOARDING HOUSE IN PONOROGO - Indah Puji Astuti; Dewangga Febrianus Rosidin; Andy Triyanto (PISSN, 2021)
The need for a place to live or a boarding house is very important, especially for immigrants. Students who want to continue to a higher level as well as workers have the most important needs when deciding to continue their education or looking for work in Ponorogo, namely looking for a place to live or a boarding house. With these conditions where there are many seekers of boarding houses, it makes people who have land to live in thinking about making boarding houses for students or workers. To find information on boarding places, boarding house seekers must quickly get information related to places that rent out boarding rooms. It is very time consuming if you have to go to boarding houses one by one. The purpose of this research is to make a prototype application for finding and ordering boarding houses in Ponorogo to make it easier for boarding house seekers to find information related to boarding houses that match what they want without having to go to one place. As for the boarding house owners help recommend their boarding house. The stages in this research adopt the Waterfall system development method which consists of analysis, design, line program creation, and system testing. The results of this study indicate an accuracy value of 100%, namely the tests carried out on the application prototype show that the application can run well according to its functionality. Keywords: Android, Boarding house, Waterfall, application, prototype